Toxic chromium in water and the effects on the human body: a systematic review. (26th December 2022) - Georgaki, Maria-Nefeli; Charalambous, Marianna
Abstract: Both in developed and developing countries, there is a growing concern about the dangerous hexavalent chromium, in the consumption of drinking water. Hexavalent chromium is recognized to have a negative impact on the human body, both in the short and long term. The purpose of this study is to evaluate the relationship between hexavalent chromium in water and its impact on human health. A systematic review of the international literature is applied, according to the instructions of PRISMA protocol, in the databases PubMed and Scopus, for the years 2005–2022. The systematic literature review was conducted using inclusion and exclusion criteria, and appropriate keywords for exposure and outcome. A total of 18 studies met all inclusion criteria. Most research concludes that hexavalent chromium is a risk factor for humans, as opposed to trivalent chromium who is a protective factor. A study indicates the consumption of drinking water with high concentrations of hexavalent chromium, as a protective factor for human life, while eight of the total studies suggest hexavalent chromium as a potential risk factor. It is necessary to clarify the origin, the mode of action, and the negative impact has on human health, to create appropriate preventive and intervention measures. HIGHLIGHTS: Assessment of the relationship between harmful hexavalent chromium in water and human health effects (systematic review – PRISMA protocol). Data on hexavalent chromium from an epidemiological point of view. A study indicates the consumption of drinking water with high concentrations of hexavalent chromium is a protective factor for human life. Eight of the studies suggest hexavalent chromium as a possible risk factor. Graphical Abstract